Program Kesiapsiagaan Tsunami Usaha Hotel di Kawasan Pariwisata Anyer, Provinsi Banten - Shandra Rama Panji Wulung; Cep Ubad Abdullah (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2021)
Increased tourism activity and the vulnerability of the Anyer tourism area on the coast of the Sunda Strait triggered the development of hotel preparedness for disaster risk reduction. The safety and security of tourists is the main focus of stakeholders, especially the hotel in realizing the coastal area of the Sunda Strait as a tsunami-resistant area. This study aims to identify tsunami preparedness programs for hotels in the tourism area of Anyer, the government programs of the Banten Province, and Serang Regency were also identified. Primary data were obtained through observation, in-depth interviews, and questionnaires, while secondary data were obtained through previous studies and local government policies. Data were analyzed using qualitative analysis methods. This study was carried out for six months in eight hotels in the Anyer tourism area. The results showed that hotels in the Anyer tourism area had not implemented the non-structural preparedness concept according to the tsunami ready hotel concept before the Sunda Strait Tsunami. The absence of standard tsunami operational procedures is one of the biggest causes of the number of casualties.